Investigasi Potensi Agregat Geoteknik Dengan Metode Geolistrik (Investigation of Potential Geotechnical Aggregate With Using Geoelectrical Methods) - Rusli, Muhammad (Jurusan Teknik Pertambangan FT UBB, 2015)
Geotechnical Aggregate are rocks that can be used as material for a wide range of construction engineering purposes. The need for geotechnical aggregates increased along with the rapid development. Required sources of aggregatequalified engineering was good, close to the project site and has large reserves. This research will be carried out an investigation to get to the source of geotechnical aggregate surveying of Geology and Geophysics measurements. Geophysical measurement is working by using of Geoelctric methods with Schlumberger configuration. Geological survey result obtained is that the material consists of geotechnical aggregate are QTV , Qtvl and TMV , composition form clastica volcanic rocks , breccias , lava , tuff andesite to basalt. Result of Geoelectric measurements showed that the potential for geotechnical aggregate form Alluvial rocks having resistivity values between 2-20 ohm meter , whereas the geotechnical aggregate form intrusive rocks is 30-80 ohm meter . Resource potential Probable amounted to 5,742,453 m3 . Keywords: Aggregate geotechnical, Geolistrik, Schlumberger, Resource.